Safety and Efficacy of Totally Percutaneous Access Compared With Open Femoral Exposure for Endovascular Aneurysm Repair: A Meta-analysis. (April 2017) - Cao, Zhanjiang; Wu, Weiwei; Zhao, Keqiang; Zhao, Junlai; Yang, Yu; Jiang, Chao; Zhu, Rongrong
Purpose: To compare the safety and efficacy of percutaneous (PEVAR) vs open femoral access (OFA) techniques for endovascular aneurysm repair (EVAR).Methods: A systematic review of English-language articles (Medline, EMBASE, and Cochrane databases) between January 1999 and August 2016 returned 11 studies including 1650 patients with 2500 groin accesses eligible for the meta-analysis. Data extracted from each study were synthesized to evaluate technical success rates, procedure time, and complications for the 2 access approaches. Data are presented as the odds ratio (OR) or mean difference (MD) with 95% confidence intervals (CI). The quality of individual studies was evaluated based on the Newcastle-Ottawa scale.Results: The mean technical success rate in the PEVAR group was 94.5% (785/831). The overall OR was 0.38 (95% CI 0.12 to 1.18, p=0.09), indicating no significant difference between the methods. The procedure time in PEVAR was shorter than OFA (mean difference −24.52, 95% CI −46.45 to −22.60, p<0.001). Overall, the total complication rate was 15.3% in the OFA group vs 7.8% in the PEVAR group (OR 0.52, 95% CI 0.37 to 0.73, p<0.001). The meta-analysis identified significant differences between groups for all complications (p<0.001) and the following individual adverse events: wound infection (OR 0.28, 95% CI 0.10 to 0.81, p=0.02), pseudoaneurysm (OR 8.07, 95% CI 1.54 to 42.32, p=0.01), seroma (OR 0.10, 95% CI 0.02 to 0.55, p=0.008), and lymphocele or lymph leak (OR 0.19, 95% CI 0.04 to 0.92, p=0.04).Conclusion: PEVAR had a similar technical success rate, shorter procedure time, and lower complication rate compared with OFA. Thus, percutaneous access appears to be the preferential approach for EVAR. However, larger and randomized studies are needed to draw definitive conclusions.